The effect of corporate social responsibility disclosure and corporate governance on aggressive tax action - I Made Pradana Adiputra; Dwi Martani; I Putu Hendra Martadinata (Universitas Hayam Wuruk Perbanas, 2019)
This study aims to analyze the effect of corporate social responsibility disclosure and corporate governance on aggressive tax action. This study analyzes corporate social responsibility disclosure based on Global Reporting Initiative (GRI), corporate governance analysis using ASEAN Corporate Governance Scorecard and measurement of aggressive tax action by using abnormal book tax difference (ABTD). It was conducted using secondary data in the form of annual reports and financial statements of companies listed on the Indonesia Stock Exchange in 2012- 2014. Sampling was done by purposive sampling, with nonprobability method. The sample was determined based on companies disclosing corporate social responsibility in accordance with content analysis on GRI4. The data were analyzed using regression analysis for testing the research model. It shows that the disclosure of corporate social responsibility negatively affects aggressive tax action. It also shows that corporate governance through corporate boards can reduce aggressive tax action, while the audit committee and internal audit have small effect on the tendency of aggressive tax action. This means the government can strengthen and enforce policies related to social responsibility and corporate governance to prevent tax aggressive behavior by companies.